Risk Profiles for Falls among Older Adults: New Directions for Prevention - Satariano, William A.; Wang, Constance; Kealey, Melissa E.; Kurtovich, Elaine; Phelan, Elizabeth A. (Frontiers in Public Health, 2017)
Objective: To address whether neighborhood factors, together with older adults’ levels of health and functioning, suggest new combinations of risk factors for falls and new directions for prevention. Method: This is a cross-sectional study of 884 people aged > 65 years from Alameda County CA, Cook County IL, Allegheny County PA, and Wake and Durham counties NC. Interviews focused on neighborhood characteristics, physical and cognitive function, walking, and falls and injuries. Four risk profiles (higher-order interactions of individual and neighborhood factors) were derived from Grade-of-Membership (GoM) analysis. Results: Profiles 1 and 2 reflect previous results showing that frail older adults are likely to fall indoors (Profile 1); healthy older adults are likely to fall outdoors (Profile 2). Profile 3 identifies the falls risk for older with mild cognitive impairment living in moderately walkable neighborhoods. Profile 4 identifies the risk found for healthy older adults living in neighborhoods with low walkability. Discussion: Neighborhood walkability, in combination with levels of health and functioning, is associated with both indoor and outdoor falls. New directions for prevention, based on individual and neighborhood factors, are addressed.